Reflexões a partir da perspectiva dos letramentos críticos : a experiência em aulas de língua espanhola no CEL-SP - Carvalho Pinto, Emily de (Universidade Federal de São Carlos, 2016)
This Master's degree research aims to analyze the perception, reception and evaluation of students and the teacher-researcher regarding activities employed from the perspective of Critical Literacies. Theoretical aspects are based on authors like Monte Mór (2008, 2014, 2015), Lankshear and Knobel (2003, 2007), Duboc (2012, 2014), Duboc and Gattolin (2015), Kalantzis and Cope (2008, 2012), Rojo (2009, 2012), Janks (2012, 2013), Janks and Vasquez (2011), Freire (2011), Cervetti et. alii. (2001) and Jordão (2010; 2014), who report the possibility of developing critical features and agency of individuals accounting for the local context. Besides, we seek for understanding considerations about the post-method through Kumaravadivelu (2006) and Abrahão (2009) in order to analyze participants' autonomy development and issues related to teaching practices. Furthermore, we search to find focal points between the two perspectives mentioned before. Considering the qualitative nature of this study, it is under the methodology of a research-action according to Burns (1999; 2010) and Viana (2007), as it takes place in an environment in which the teacher rethinks her practice. The tools used were: survey, aiming to profile and understand the interests of students; the record book of the teacher-researcher, self-evaluation sheets and audio recording of the lessons. These tools enable us to observe the perception of the participants about teaching units, the progress of activities, the attitude of the teacher-researcher, the gaps that took place in the classroom and the curricular attitude of the teacher-researcher before these gaps. The research was carried out at a State Language Study Center, in the state of São Paulo, located in a public school in a small town in the countryside. The organization and analysis of data allowed a reading which indicates the strategies used by the teacher-researcher to improve Critical Literacies and we observe: a) material elaboration; b) perception of the gaps; c) curricular attitude and d) autonomy/agency development. Also, it was possible to observe the improvement of critical features in some participants and as they found it strange, they deconstruct and took different positions as from the discussions regarding the proposed themes.

Esta investigación de maestría tiene como objetivo analizar la percepción, la recepción y la evaluación que alumnos y profesora-investigadora tuvieron de actividades desarrolladas a partir de la perspectiva de las literacidades críticas. Los aspectos teóricos están basados en los siguientes autores: Monte Mór (2008, 2014, 2015), Lankshear e Knobel (2003, 2007), Duboc (2012, 2014), Duboc e Gattolin (2015), Kalantzis e Cope (2008, 2012), Rojo (2009, 2012), Janks (2012, 2013), Janks e Vasquez (2011), Freire (2011), Cervetti et. alii. (2001), Ferreira e Takaki (2014) e Jordão (2010; 2014), quienes nos explican la posibilidad de desarrollar la criticidad y la agencia de los sujetos, considerando el contexto local. Además de esto, buscamos comprender las consideraciones sobre la perspectiva del post-método a través de Kumaravadivelu (2006) e Abrahão (2009) para analizar el desarrollo de la autonomía de los participantes y las cuestiones relacionadas a la práctica docente, así como encontrar puntos de aproximación entre ambas perspectivas. Considerando la naturaleza cualitativa de esta investigación, este trabajo científico se encuadra en los estudios de investigación-acción Burns (1999; 2010) y Viana (2007), ya que se trata de un contexto en que el profesor repiensa su práctica profesional. Utilizamos como instrumentos: cuestionarios para trazar el perfil e interés de los alumnos, diario de la PP, fichas de autoevaluación y grabaciones de las clases. Por medio de éstos, pudimos observar la percepción de los sujetos relacionados con las unidades didácticas, el desarrollo de las actividades, la postura de la profesora-investigadora, las grietas que emergieron de la clase y la actitud curricular de la profesora-investigadora frente a esas grietas. El contexto de la investigación es un Centro de Estudios de Lenguas (CEL) estatal, ubicado en una escuela pública de una ciudad del interior paulista (SP). La organización y el análisis de los datos permitieron una lectura que indica cuáles estrategias fueron utilizadas por la profesora-investigadora para desarrollar las literacidades críticas, donde encontramos: a) la preparación del material; b) la percepción de las grietas; c) la actitud curricular y d) el desarrollo de la autonomía/agencia. Además de esto, fue posible observar el desarrollo de la criticidad de algunos participantes y como se sintieron frente a ello, donde también descontruyeron y se reposicionaron a partir de las discusiones de los temas propuestos.
Reflexiones a partir de la perspectiva de las literacidades críticas : la experiencia en clases de lengua española en el CEL-SP
Keywords: Letramentos críticos; Pós-método; Ensino de espanhol; Escola pública; Material didático.; Literacidades críticas; Post-método; Enseñanza de español; Escuela pública; Material didáctico.; Critical literacies; Post-method; Teaching spanish; Public school; Teaching material.; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA